1981
DOI: 10.1007/bf02402848
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical framework for the compressive properties of aligned fibre composites

Abstract: New experimental results have made necessary the reformulation of the theory for compressive strength. The new theory is based on the precept that a number of different mechanisms can cause composite ifailure. The active one in a particular situation is that which gives the lowest failure stress. Thus composite strength can be dominated by fibre strength when the fibres are ductile, or controlled by matrix yielding when the matrix is soft. Lack of linearity in the fibres has a very important effect also, as do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(13 citation statements)
references
References 9 publications
(14 reference statements)
2
11
0
Order By: Relevance
“…An interesting observation is that the same type of glass composite changes it's failure mode when tested under different loading ratios. This observation was also made by Piggott (1981) who found that the failure mode changed when the composites were tested under pure compression with partially cured matrix. The reason for the change in failure mechanism can be attributed to the magnitude of the shear modulus of the matrix and hence the composite.…”
Section: Effect Of Loadingsupporting
confidence: 63%
See 4 more Smart Citations
“…An interesting observation is that the same type of glass composite changes it's failure mode when tested under different loading ratios. This observation was also made by Piggott (1981) who found that the failure mode changed when the composites were tested under pure compression with partially cured matrix. The reason for the change in failure mechanism can be attributed to the magnitude of the shear modulus of the matrix and hence the composite.…”
Section: Effect Of Loadingsupporting
confidence: 63%
“…The splitting failure mode in glass composites has been reported by Piggott (1981); Piggott and Harris (1980), Lee and Waas (1999) and . Splitting is a distinctly different failure mechanism from kinking.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations